Thrombolytic therapy in a patient with inferolateral myocardial infarction after carbon monoxide poisoning. (January 2016) - Unlu, M; Ozturk, C; Demirkol, S; Balta, S; Malek, A; Celik, T; Iyisoy, A
Introduction: ST segment elevation myocardial infarction (STEMI) due to coronary artery occlusion caused by intracoronary thrombosis in the setting of acute carbon monoxide (CO) poisoning is a very rare presentation. We present a case of intracoronary large and mobile thrombus formation after CO poisoning. Case presentation: A previously healthy 50-year-old woman was referred for CO poisoning. She had chest pain after exposure to CO. Her initial mental status was preoccupied with chest pain. Her initial CO fraction was 28.1%, and initial laboratory data showed creatine kinase–myocardial isoenzyme of 134 U/L (upper limit 25 U/L) and troponin I of >50 ng/mL (upper limit 0.06 ng/mL). Electrocardiography was carried out on admission, revealing an ST segment elevation in the inferolateral leads. After initial evaluation, coronary angiography was performed and an intracoronary large mobile thrombus was seen in the proximal left anterior descending (LAD) artery with no significant stenosis. We administered tenecteplase with heparin. After the thrombolytic therapy, ST elevation in the inferolateral leads resolved. Repeat angiography was performed after 24 h; the thrombus in LAD had resolved. The patient was discharged after 5 days, with persistent Q wave in the inferior leads and mild hypokinesia of the inferoposterior wall suggesting myocardial injury. Conclusion: We describe intracoronary thrombus formation induced by CO poisoning. Because intracoronary thrombus can result in myocardial infarction, its consideration following CO poisoning is important. Patients with CO poisoning who have symptoms of STEMI should be carefully evaluated with serial electrocardiograms, cardiac biomarkers, and an echocardiogram. When there is evidence of acute myocardial injury, a primer in coronary angiography can determine which patients could benefit from intervention.